English Major Students' Preference Towards the Language Teaching Methods Used by English Language Instructors at Hebron University - Mohammed Farrah; Rose Shawkat Hijjih (Randwick International of Education and Linguistics Science Journal, 2024)
Teaching methods have an impact on the learning process and it may or may not be useful for the students. This study explores the preferred teaching methods of English language used by English language instructors among a sample of English major students from Hebron university in Hebron, Palestine. 100 participants took part in this study. They are between 18 and 28 years old. Regarding their gender, eighty-four are females and sixteen are males from different levels of study. The study employed a quantitative research methodology. The researchers used a 15-item questionnaire to gather data. SPSS was used to analyze the data. Finding shows that the students prefer using communicative activities (Mean=3.34) and using technology (Mean=3.29) in the teaching process. The researchers concluded with a number of recommendations. The teachers should make a combination of teaching methods and techniques. Thus, the method will be successful, more effective and makes the teaching process efficient. In general, the results of the study may help instructors to become more professional and this is going to be reflected in their students' performance.